Knowledge and behaviour towards salt intake among adult patients getting treatment in outpatients Clinic Hospital USM - Zaki, Farah Syazwani Hilmy (Universiti Sains Malaysia, 2016)
Sodium chloride (salt) is widely used in people’s food as an additive or preservatives to make food tastes better and lasts longer. The knowledge and behaviour towards sodium chloride (salt) intake has become a question mark. The aim of this study is to determine the knowledge and behaviour towards sodium chloride (salt) intake among adult patients getting treatment in Outpatients Clinic Hospital USM. A cross-sectional study was conducted on 186 adult patients getting treatment at Outpatients Clinic Hospital USM, using convenience sampling. A pilot study was conducted using Pan American Health Organization (PAHO) questionnaires. The questions contains dichotomous and Likert scale questions types, thus yielded higher Standardized Items Chronbach’s Alpha compared to Chronbach’s Alpha. Knowledge towards sodium chloride (salt) intake yielded Standardized Items Chonbach’s Alpha of 0.520 and Chronbach’s Alpha of 0.387. Behaviour towards sodium chloride (salt) intake yielded Standardized Items Chonbach’s Alpha of 0.519 and Chronbach’s Alpha of 0.394. There was no significant association between knowledge and behaviour towards sodium chloride (salt) intake using independent t-test, p-value=0.136. However, there is a significant association between knowledge towards sodium chloride (salt) intake with education level using One Way ANOVA, p-value=0.002, and there is a significant association between knowledge towards sodium chloride (salt) intake with gender using Independent t-test, p-value=0.012. In conclusion, the findings showed that knowledge and behavior does not affect the intake of sodium chloride (salt) and future research with larger sample size should be conducted.